2000
DOI: 10.1155/2000/86281
|View full text |Cite
|
Sign up to set email alerts
|

From the ECM to the Cytoskeleton and Back: How Integrins Orchestrate T Cell Action

Abstract: Brugge, 1995;Schwartz et al., 1995;Shimizu et al., 1999;Hynes and Bader, 1997;Hynes, 1996). Several aspects of integrin structure and function lead to their prominent role in regulating the ability of a T cell to interact with and respond to the extracellular environment. First, the short cytoplasmic tails associate with cytoskeletal proteins, such as talin, o-actinin and paxillin (Clark and Brugge, 1995). In this way, integrins act as a cell surface bridge that links the structure of the extracellular matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 131 publications
0
10
0
Order By: Relevance
“…We also found that the expression of active form of H-Ras induces the activation of the ␤ 1 in B cells (16). Accumulating evidence demonstrates that PI3K appears to play a central role in integrin triggering (27,32,33). One plausible explanation for such discrepant and complex nature of H-Ras functions can be considered to be that second signals induced by H-Ras may be differently involved in "on and off switch" for integrin triggering.…”
Section: Discussionmentioning
confidence: 57%
“…We also found that the expression of active form of H-Ras induces the activation of the ␤ 1 in B cells (16). Accumulating evidence demonstrates that PI3K appears to play a central role in integrin triggering (27,32,33). One plausible explanation for such discrepant and complex nature of H-Ras functions can be considered to be that second signals induced by H-Ras may be differently involved in "on and off switch" for integrin triggering.…”
Section: Discussionmentioning
confidence: 57%
“…Therefore, the lack of sufficient intracellular signaling in the neonatal lymphocytes may interfere with efficient transendothelial migration. Recent studies have reported that transendothelial migration of leukocytes is regulated by integrin-mediated, calciumdependent, cytoskeletal organization (37,38). Therefore, a defect in calcium mobilization in neonatal lymphocytes may not preclude efficient adhesion to endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Integrins are one of the major families of adhesion molecules that mediate cell-ECM and cellcell interactions (2). Adhesion of T cells to ECM proteins or cellular integrin ligands is fundamental for lymphocyte development, migration, extravasation, and activation (3,4). Among the integrin family members, LFA-1 (a L /b 2 , CD11a/CD18) is essential for lymphocyte homing in lymphoid and nonlymphoid tissues, transmigration, and antigen-specific T-cell responses (3).…”
Section: Introductionmentioning
confidence: 99%